Core-Plasma Pattern Partnership Agreement with Micro-Small Business based on the Perspective of Competition Law - Tri Anggraini, Anna Maria; Kerti, Renti Maharaini; Sabirin, Ahmad (International Journal of Law and Public Policy (IJLAPP), 2023)
Partnership agreements that aim to mutually benefit both parties, especially empowering micro and small businesses, often have unfavorable consequences for parties whose bargaining position is weak, so that the business competition authority is also given supervisory authority over the implementation of the agreement. The imbalance in bargaining position in this agreement is the reason for writing to raise the issue of understanding owning and/or controlling micro and small businesses according to the applicable regulations and how it is implemented in the nucleus plasma partnership scheme for the oil palm plantation sector. This normative research includes prescriptive research using secondary data which is analyzed qualitatively and concluded using deductive methods. The results of this study indicate that the notion of having is defined as ownership of equity or capital, while the term control focuses more on managerial control which ultimately has an impact on asset control. The partnership agreement contains several clauses that have the potential to own and/or control micro-small businesses according to Law 20/2008 jo. Law 11/2020, besides that, it also has the potential to violate the provisions or principles of unfair business competition. However, this potential violation is difficult for competition authorities to reach due to the absence of technical regulations that explain the meaning of owning and/or controlling micro and small businesses. Therefore, KPPU needs to prepare further regulations in the form of guidelines that explain the limitations.